A Study of Serum Creatinine and Urea in Adult Female Individuals and their Correlations with BMI (Journal of Rangpur Medical College, 2022)
Background: The World Health Organization has announced overweight and obesity as a global epidemic that has strong associations with renal function impairment.Objectives: To evaluate the serum creatinine and urea status in adult female individuals with previous normal renal function and to observe the correlation of serum creatinine and urea with body mass index (BMI).Methods: This cross-sectional analytical study was conducted in the Department of Physiology, Rangpur Medical College, Rangpur. After briefing about the objectives, adult female subjects who met the inclusion and exclusion criteria were enrolled in the study with permission. The study included 90 subjects who were divided into three groups- apparently healthy adult females with normal weight (Group-A), apparently healthy overweight adult females (Group-B), and apparently healthy obese adult females (Group-C). The subjects were selected from different areas of Rangpur city. Their body mass index, serum creatinine, and urea were measured. For statistical analysis, one way ANOVA (post-Hoc) test and Pearson’s correlation coefficient test were performed as applicable by computer-based SPSS-25.0 for windows. Regarding the interpretation of results, p_0.05 was accepted as significant.Results: The mean serum creatinine level was significantly (p_0.001) higher in overweight and obese female adults than in normal-weight female adults. It was also significantly (p_0.05) higher in obese female adults than in overweight female adults. Again, the mean serum urea level was significantly (p_0.05) higher in overweight female adults than normal-weight female adults and in obese female adults than in overweight female adults. It was also significantly (p_0.001) higher in obese female adults than in normal-weight female adults. This study also found highly significant (p_0.001) positive correlation of serum creatinine (r=0.499) and urea (r=0.396) with body mass index.Conclusion: Serum creatinine and urea were elevated in overweight and obese female adults and both parameters were positively correlated with BMI. Regular body mass index screening is recommended to assess body weight easily and effectively.J Rang Med Col. September 2022; Vol. 7, No. 2:25-30